NILAI DAYA HANTAR LISTRIK, KADAR ABU, NATRIUM, DAN KALIUM PADA MADU BERMERK DI PASARAN DIBANDINGKAN DENGAN MADU ALAMI (LOKAL) - Setya Sri Antary, Putu; Ratnayani, Ketut; Mayun Laksmiwati, A. A. I. A. (Jurnal Kimia (Journal of Chemistry), 2013)
Honey sweet substance naturally produced by bees. Good honey must meet the requiremends setby the Indonesian National Standard (SNI). The aim of this research was to determine thequality of some branded honey samples sold in some markets around Denpasar and natural honey (local) collected from beekeepersby examining their electrical conductivities, ash contents, and ratio of potassium to sodium. The electrical conductivities were determinedby applying the standard procedures established by IHC (International Honey Commission), ash contents were quartified by following the procedures of standard SNI01-3545-2004, while the determination of potassium and sodium contents were carried out by the use of Atomic Absorption Spectrophotometry. The results showed that the electrical conductivities and ash contentsin all honey samples studiedmet the maximum limits of standard values which were of 0.8 mS.cm -1 and 0.50 %, respectively. The results also demonstrated that the value of electrical conductivities were proportional to the ash contents. The ratio of sodium to potassium of a good quality honeyis approximately 4 : 1. In this research, it was found that the ratio of Na : K for samples A (natural honey), B, C, and D, were of (3 : 1), (2: 1), (4 : 1), and (4 : 1), respectively, while for sample E was of 8 : 1. It was concluded that A, B, C, and D samples meet the criteria of good quality honey, while sample E (not branded honey) didnot meet the criteria.
Keywords: ash content, electrical conductivity, Atomic Absorption Spectrophotometry (AAS), the ratio of sodium and potassium